Drowning in Oil : BP and the Reckless Pursuit of Profit - Steffy, Loren C. (New York McGraw-Hill Professiona, 2011)
A detailed analysis of the catastrophe on the oilrig Deepwater Horizon, and the history of BP and aftermath of the company trying to manage the crisis
Include Index
Keywords: Petroleum industry and trade -- Gulf of Mexico -- Nature--Effect of human beings on